A new species of Trichoscelia Westwood (Neuroptera: Mantispidae) from northern South America - Machado, Renato Jose Pires (Zootaxa, 2018)
A new species of Trichoscelia Westwood (Mantispidae: Symphrasinae) is described herein, T. geraldoi n. sp. This is the 16th species classified within the genus and presents a quite unusual body color pattern for the group. A key for the South American species of Trichoscelia and a checklist of the Symphrasinae species are presented.